Ration Formulation of Native Chicken from Fruit Fly (Drosophila melanogaster L.) and Water Hyacinth Flour (Eichornia crasipess (Mart.) Solms) - Febiola Najoan; Herry Sumampouw; Yermia Mokosuli (Indonesian Biodiversity Journal, 2022)
Fruit flies and water hyacinths are believed to be able to increase body weight in native chickens because they have a relatively high protein content. This study aims to determine the effect and dose of fruit fly (Drosophila melanogaster L.) with a combination of water hyacinth flour (Eichornia crassipes (Mart.) Solms) for consumption and body weight gain in native chickens (Gallus domesticus L.). The method used in this study used a Completely Randomized Design (CRD) method. Where this study was an experimental study using five treatments and four replications. The results showed that the average consumption of free-range chicken rations was 30.41 g per head per week, where P1 was the highest ration consumption at 6.75 g per head per week, and the lowest was at P4 at 5.72 g per head per week. On body weight gain, native chickens had an average of 11.42 g per head per week, where P2 had the highest average of 2.39 g per head per week and P1 with the lowest average of 2.13 grams per week. The consumption of free-range chicken rations tends to increase along with the composition of water hyacinth in the ration to 7.5%.